2018
DOI: 10.3201/eid2402.171018
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Pediatric Ebola Predictive Score, Sierra Leone1

Abstract: We compared children who were positive for Ebola virus disease (EVD) with those who were negative to derive a pediatric EVD predictor (PEP) score. We collected data on all children <13 years of age admitted to 11 Ebola holding units in Sierra Leone during August 2014–March 2015 and performed multivariable logistic regression. Among 1,054 children, 309 (29%) were EVD positive and 697 (66%) EVD negative, with 48 (5%) missing. Contact history, conjunctivitis, and age were the strongest positive predictors for EVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…One study assessed WHO 2014 case definitions for a paediatric population (younger than 13 years old); the sensitivity was 98•0% (95% CI 95•0-99•0) and specificity was 5•0% (3•0-7•0). 25 When WHO subdefinitions were assessed, history of contact and symptoms had high specificity compared with clinical symptoms alone, ranging from 62•3% (95% CI 49•8-73•5) to 94•4% (95% CI not provided in original paper; table 2). The highest sensitivity (100•0%) was documented for the WHO subdefinitions in which fever was not mandatory.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…One study assessed WHO 2014 case definitions for a paediatric population (younger than 13 years old); the sensitivity was 98•0% (95% CI 95•0-99•0) and specificity was 5•0% (3•0-7•0). 25 When WHO subdefinitions were assessed, history of contact and symptoms had high specificity compared with clinical symptoms alone, ranging from 62•3% (95% CI 49•8-73•5) to 94•4% (95% CI not provided in original paper; table 2). The highest sensitivity (100•0%) was documented for the WHO subdefinitions in which fever was not mandatory.…”
Section: Resultsmentioning
confidence: 97%
“…One was excluded because it is yet unpublished (FG). Of the 14 included studies, 11 were full manuscripts, 5,6,22,24,25,27,[29][30][31][32][33] one a letter, 28 one an oral plenary abstract, 26 and one a conference poster 23 (the author of this poster was also contacted and they provided an abstract with additional data [ (seven in Sierra Leone, 5,6,25,26,30,32,33 four in Guinea, 24,27,28,31 and two in Liberia 23,29 ). The remaining article was published in May, 2010, assessing Marburg virus in Angola.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sensitive and specific clinical case definition for EVD in children would allow rapid access to appropriate treatment for children with EVD, crucial when early mortality is so high, and also protect children without EVD (with a different illness) from exposure to EVD while awaiting laboratory test confirmation. To date there has been only one attempt at deriving a paediatric-specific case definition using multicentre data on over 1000 children from the West African outbreak, and this case definition has not yet been validated on wider datasets [ 106 ]. It also does not include malaria rapid diagnostic test results which have been shown to be an important discriminator in a mixed age study [ 107 ].…”
Section: Suspect Ebola Virus Disease Case Definition In Childrenmentioning
confidence: 99%
“…19 A recent systematic review concluded that the validity of existing paediatric triage tools is uncertain and that none are likely to be reliable in resource-constrained environments, with the lack of follow-up data for children not admitted highlighted as a major limitation of current research in this field. 20 While some disease-specific tools have been developed, [21][22][23] their application is limited as it is often only possible to ascertain a microbiological cause in a minority of febrile children.…”
Section: Introductionmentioning
confidence: 99%